EDUKASI DAN SOSIALISASI SERTIFIKASI HALAL BAGI MASYARAKAT MUSLIM PELAKU UMKM GUNUNGPUTRI BOGOR - Warto; Sabik Khumaini; Rizkiyah Amelia; Fina Andrianti (Jurnal Istimā, 2025)
This community education programme aimed to enhance the understanding of Muslim communities and MSME actors regarding the principles of halal–haram jurisprudence and the procedures for obtaining halal certification. The activity was conducted on 12 March 2025 at Al-Amin Bumi Mutiara Mosque, Gunungputri, Bogor, involving 40 participants and three MSMEs. The programme employed interactive lectures, case-based discussions, and technical mentoring. The results indicate a significant increase in participants’ knowledge of the fundamental principles of halal–haram, halal production processes, and the steps required for halal certification submission. Participants demonstrated strong engagement throughout the sessions, and five MSME owners expressed their readiness to initiate the halal certification process. Overall, the programme shows that structured education effectively promotes awareness and strengthens community commitment to implementing halal product assurance.